Implementation of PSAK 109 In Zakat Management Organizations In Indonesia: A Critical Review Of Transparency, Accountability, And Implementation Challenges - Putriku Najla Qatrunnada; Aqila Nurul Aziza; Calista Raihana Chandra; Siti Munawaroh; Aulia Nasha Ammara; ⁠Rhonovan; Alif Syafwan Surya Hamid; Harsono Edwin Puspita (Muhasabatuna : Jurnal Akuntansi Syariah, 2026)
This study is a literature review of the implementation of Financial Accounting Standards Statement (PSAK) Number 109 concerning Accounting for Zakat, Infaq, and Alms in Zakat Management Organizations (OPZ) in Indonesia. This standard was published by the Indonesian Institute of Accountants (IAI) in 2011 as a guide for the National Zakat Agency (BAZNAS) and Zakat Management Institutions (LAZ) in recognizing, measuring, presenting, and disclosing ZIS transactions in an orderly and accountable manner. This article reviews a number of empirical studies and conceptual studies published in the period 2015–2025 to identify compliance patterns, supporting factors, obstacles, and the implications of implementing the standard on the quality of OPZ financial reporting. The review results indicate that although most OPZs have implemented the main components of PSAK 109, especially in the recognition and measurement aspects, many disclosure aspects in the Notes to the Financial Statements (CALK) still do not meet the standard requirements. The limited number of competent human resources in the field of sharia accounting, weak accounting information systems, and suboptimal external supervision are the main challenges that need to be addressed immediately.